UMP signed an MOU with Japanese company to develop coating products - UMP, PNC (Pejabat Naib Canselor, 2016)
Universiti Malaysia Pahang (UMP) would be collaborating with Japanese company, Eco 24 Co. Ltd, which developed environment-friendly coating products for various industrial uses.